2005
DOI: 10.1111/j.0737-1209.2005.220504.x
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Quarantine for Individuals Affected by SARS in Toronto

Abstract: Public Health has a dual role of monitoring compliance and providing support to people in quarantine. This study has implications for public health policy and practice in planning for future public health emergencies in terms of the information and the resources required to mount an effective response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
395
2
22

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(468 citation statements)
references
References 22 publications
30
395
2
22
Order By: Relevance
“…Similar effects of isolation were found in people who had exposure to the disease during the outbreak in Toronto, Canada (Cava et al. , 2005a, b).…”
Section: Discussionsupporting
confidence: 54%
“…Similar effects of isolation were found in people who had exposure to the disease during the outbreak in Toronto, Canada (Cava et al. , 2005a, b).…”
Section: Discussionsupporting
confidence: 54%
“…In addition to identifying common themes about the experience of being quarantined, which are reported elsewhere (Cava, Fay, Beanlands, McCay, & Wignall, in press), the themes of risk perception and reported compliance and the relationship between them were important findings of the study. We defined risk perception as participants' beliefs about their level of risk of contracting or spreading SARS.…”
Section: Resultsmentioning
confidence: 90%
“…Few reported positive feelings: 5% (48) reported feelings of happiness and 4% (43) reported feelings of relief. Qualitative studies also iden tified a range of other psy chological responses to quar antine, such as confusion, [11][12][13]23 fear, [12][13][14][15]23,24 anger, 12,13 grief, 29 numbness, 23 and anxietyinduced insomnia. 14,15 One study compared undergraduates who had been quarantined with those not quarantined immediately after the quarantine period and found no significant difference between the groups in terms of posttraumatic stress symptoms or general mental health problems.…”
Section: The Psychological Impact Of Quarantinementioning
confidence: 95%
“…A study 25 been quar antined avoided people who were coughing or sneezing, 26% (255) avoided crowded enclosed places, and 21% (204) avoided all public spaces in the weeks following the quarantine period. A qualitative study 13 reported that several participants described longterm behavioural changes after the quarantine period, such as vigilant handwashing and avoidance of crowds and, for some, the return to normality was delayed by many months.…”
Section: The Psychological Impact Of Quarantinementioning
confidence: 99%
See 1 more Smart Citation